Assessing the impacts of implementing lean construction - Alarcón,Luis F (Pontificia Universidad Católica de Chile. Departamento de Ingeniería y Gestión de la Construcción, 2008)
Over the last 10 years an increasing number of companies have implemented lean construction practices in an attempt to improve performance in construction projects. Most companies, and also some researchers, have reported satisfactory results from their implementation. However, there is still a need to provide more extensive analysis of the empirical evidence available to assess the impact of the implementation of lean construction. The authors have researched the implementation of the Last Planner System and other Lean Construction techniques in over one hundred construction projects over the last five years. They have also developed strategies and support tools for implementation. This paper analyzes some of the main impacts observed in the studied projects, and some of the lessons learned from implementations. The paper discusses difficulties and barriers for implementation, productivity improvements, variability reduction and effectiveness of implementation strategies. The paper also provides recommendations for future implementation and research